Applied Behavior Analysis Fifty Case Studies in Home, School, and Community Settings - Maich, Kimberly; Levine, Darren; Hall, Carmen; SpringerLink (Online service) (Cham : Springer International Publishing (Imprint), 2016)
This textbook offers real-world case studies for using Applied Behavior Analysis (ABA) to create, implement, and appraise behavior intervention programs across a variety of client situations. Its chapters are formatted for ease of use and retention and organized to focus on the core components of ABA: assessment, planning, implementation, evaluation, and research/ethics. Illustrative cases represent a diversity of problem behaviors, settings, social contexts, and life stages, and includes questions about data collection, goal setting, communication with families, and other processes of effective ABA practice. Together they emphasize not only the content knowledge involved in designing interventions, but also the interpersonal skills necessary for helping change complex challenging behaviors. These fifty case studies: Are suited to individual or team training. Present guiding questions regarding ABA process and professional practice. Feature charts, forms, templates, and other practical tools. Include links to Behavior Analyst Certification Board resources. Demonstrate the flexibility of ABA for use with children, adolescents, adults, or seniors. Applied Behavior Analysis: Fifty Case Studies in Home, School, and Community Settings is an essential text for graduate students, researchers, and practitioners in child and school psychology, behavior analysis, learning and instruction, counseling, and education. This singular volume models critical thinking and professional development in keeping with best practices and professional standards.
Part I. Assessment -- Chapter 1. Assessment Case Studies for Preschool to School-age Children -- Chapter 2. Assessment Case Studies from Adolescence to Adulthood -- Part II. Planning -- Chapter 3. Planning-Focused Case Studies for Preschool to School-age Children -- Chapter 4. Planning-Focused Case Studies from Adolescence to Adulthood -- Part III. Implementation -- Chapter 5. Implementation-based Case Studies for Preschool to School-age Children -- Chapter 6. Implementation-based Case Studies from Adolescence to Adulthood -- Part IV. Evaluation -- Chapter 7. Evaluation-centered Case Studies for Preschool to School-age Children -- Chapter 8. Evaluation-centered Case Studies from Adolescence to Adulthood -- Part V. Research and Ethics -- Chapter 9. Preschool to School-age Case Studies Constructed Around Research and Ethics -- Chapter 10. Adolescence to Adulthood Case Studies Constructed Around Research and Ethics.
Keywords: Developmental psychology; Behavioral Therapy; Child and School Psychology